185 Effect of zinc source and implant strategy on performance, carcass characteristics, and tissue mineral concentrations in finishing beef steers. (30th November 2020) - Messersmith, Elizabeth M; Boyer, Angela; Nuzback, Dennis; Hansen, Stephanie L
Abstract: A 126-d study utilized 72 Angus-cross steers (411 ± 16 kg) in a 3 × 2 factorial to examine the effects of Zn source and implant strategy on performance, carcass characteristics, and tissue Zn concentrations. All steers received 70 mg Zn/kg dry matter (DM) from ZnSO4 + 30 mg Zn/kg DM from one of three sources: zinc hydroxychloride (ZnHC), zinc glycinate (ZnG), or zinc sulfate (ZnS). Implant (IMP) strategies included: no implant (NoIMP) or Component TE-IS and Component TE-200 (IS/200) on d 0 and 57, respectively. Steers were blocked by weight into pens of 6 and fed a dry rolled corn-based diet via GrowSafe bunks. Data were analyzed using ProcMixed of SAS, with fixed effects of Zn, IMP, and the interaction. Liver and muscle collected on d -5, 14, 71, and 120 were analyzed for Zn concentration and data were analyzed as repeated measures (repeated effect = day). Steer was the experimental unit (n = 12/treatment). Final body weight and overall average daily gain tended to be decreased for ZnHC compared to ZnS, with ZnG intermediate within IS/200 (Zn × IMP; P ≤ 0.07). No interaction was observed for overall G:F or DM intake (P ≥ 0.41), but both were greater for implanted steers (P ≤ 0.01), while overall G:F was improved for ZnS compared to ZnHC and ZnG (P = 0.02). Carcass characteristics were unaffected by Zn × IMP or Zn source (P ≥ 0.12), but IS/200 improved HCW, DP, and REA (P ≤ 0.01). Implant increased liver Zn (P = 0.02) concentrations. Within IS/200 ZnG tended to have greater muscle Zn than ZnS while ZnHC was intermediate (Zn × IMP; P = 0.09), potentially indicating differences in availability of Zn source to growing muscle. These data suggest Zn source and implant influence performance and tissue Zn concentrations.